Pedantic Semantics or Strategic Discourse? The Politics of Talking about Terrorism - Sumpter, Cameron (2016)
The language chosen by leaders to discuss terrorism and extremism has the power to shape and (de)legitimise particular strategic responses. Politically incorrect discourse will only lead to politically incorrect decisions.